Optimization of a LaNiO3 Bottom Electrode for Flexible Pb(Zr,Ti)O3 Film-Based Ferroelectric Random Access Memory Applications - Yeong Uk Choi; Hyun Soo Ahn; Jung Ehy Hong; Dong In Yang; Hwa-Pyeong Lee; Dae-Yong Jeong; Minbaek Lee; Jong Hun Kim; Jong Hoon Jung (Crystals, 2023)
The direct growth of ferroelectric films onto flexible substrates has garnered significant interest in the advancement of portable and wearable electronic devices. However, the search for an optimized bottom electrode that can provide a large and stable remnant polarization is still ongoing. In this study, we report the optimization of an oxide-based LaNiO3 (LNO) electrode for high-quality Pb(Zr0.52Ti0.48)O3 (PZT) thick films. The surface morphology and electrical conductivity of sol-gel-grown LNO films on a fluorophlogopite mica (F-mica) substrate were optimized at a crystallization temperature of 800 °C and a film thickness of 120 nm. Our approach represents the promising potential pairing between PZT and LNO electrodes. While LNO-coated F-mica maintains stable electrical conductivity during 1.0%-strain and 104-bending cycles, the upper PZT films exhibit a nearly square-like polarization–electric field behavior under those stress conditions. After 104 cycles at 0.5% strain, the remnant polarization shows decreases as small as ~14%. Under flat (bent) conditions, the value decreases to just 81% (49%) after 1010 fatigue cycles and to 96% (85%) after 105 s of a retention test, respectively.